Effects of bubbles on high-temperature corrosion of helium ion-irradiated Ni-based alloy in fluoride molten salt. (15th August 2017) - Zhu, Hanliang; Holmes, Rohan; Hanley, Tracey; Davis, Joel; Short, Ken; Edwards, Lyndon; Li, Zhijun
Highlights: Combined He ion damage and FLiNaK corrosion was studied for a Ni-Mo-Cr-Fe-Si alloy. He bubbles grew and migrated towards sample bulk with increased corrosion duration. Bubble defects increased physical contact area between alloy and molten salt. Significant Si segregation at bubble surfaces was observed. Si segregation enhanced chemical corrosion damage. Abstract: Samples of a Ni-Mo-Cr-Fe-Si alloy subject to helium ion irradiation damage were corroded in a eutectic mixture of FLiNaK at 750 °C. It was found that the helium bubbles that formed increased the number of surface defects so greatly increasing the physical contact area between the alloy and the molten salt, resulting in acceleration of corrosion damage. Segregation and depletion of chemical elements at bubble surfaces were also identified, and became more severe with increasing bubble size. Significant segregation of Si resulted in the formation of Ni-Si precipitates at large bubbles. This segregation enhanced the chemical corrosion damage to the alloy.